1938
DOI: 10.1001/archpedi.1938.01980180045003
|View full text |Cite
|
Sign up to set email alerts
|

Giardiasis in Children

Abstract: Giardia lamblia belongs to the flagellates. Its name has often been changed; some clinicians still call it Lamblia intestinalis. The parasite can be found in every part of the world. A number of similar species in animals have been described, but it is still a question whether the mouse or the rat can be a host of the type of Giardia found in human beings. The incidence of the parasite was estimated at 12 per cent in the United States by Hegner and at about 10 per cent in Hungary by L\l=o"\rincz.1 The infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1939
1939
1982
1982

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Infection with Giardia may be associated with clinical and/or laboratory features suggestive of malabsorption, the extent of which is variable. This has been observed in children (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), and in adults (21, 23 -32). Geographically, giardiasis-associated malabsorption in adults has a wider distribution than that associated with tropical sprue (32).…”
mentioning
confidence: 67%
“…Infection with Giardia may be associated with clinical and/or laboratory features suggestive of malabsorption, the extent of which is variable. This has been observed in children (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), and in adults (21, 23 -32). Geographically, giardiasis-associated malabsorption in adults has a wider distribution than that associated with tropical sprue (32).…”
mentioning
confidence: 67%
“…It is not our purpose here to discuss in detail the vidence for and against the pathogenicity for man of Giardia lamblia. Those wishing for fuller references should consult papers by Lyon and Swalm (1925), Veghelyi (1938), Manson-Bahr (1940), andMcGrath, O'Farrell, andBoland (1940). Opinion is divided between those who regard this organism as a harmless parasite and those who believe that it may give rise to symptoms of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Those wishing for fuller references should consult papers by Lyon and Swalm (1925), Veghelyi (1938), Manson-Bahr (1940), andMcGrath, O'Farrell, andBoland (1940). Opinion is divided between those who regard this organism as a harmless parasite and those who believe that it may give rise to symptoms of disease.…”
Section: Discussionmentioning
confidence: 99%
“…So far as children are concerned one of the most careful of recent studies is that of Veghelyi (1938Veghelyi ( , 1940, who made observations on 92 infected and 92 control children aged 2 to 17 years at the children's clinic, Budapest. He found that in the infected subjects the occurrence of anorexia, headache, dizziness, abdominal pain, irregular bowel movement, and anaemia was much more frequent than in the controls.…”
Section: Discussionmentioning
confidence: 99%